Statistical research of retaining walls displacement on the results of geodetic measurements by analysis of variance - Schultz, R.; Annenkov, A.; Khailak, A.; Strilec, V. (KNUCA, 2014)
The analysis of geodetic measurements of retaining walls displacements in the residential quarter of the city of Kyiv is executed. For processing the observations, it was suggested to use a method of analysis of variance (ANOVA). The influence of changes displacement depending on the cycles of observations by one-factor analysis of variance is investigational. Method of one-factor ANOVA allowed also defining that for different retaining walls, a deformation process has a different dynamics. The relationship between cycles and retaining walls placement was determined using two-factor ANOVA. Method three-factor analysis of variance allowed additionally defining influence of location of deformation marks on the value of displacement. It was confirmed that the variance analysis method has great potential for the analysis of geodetic measurements, especially at the large volumes of observations.
Статистическое исследование перемещений подпорных стенок по результатам геодезических измерений методом дисперсионного анализа
Keywords: ANOVA; displacement; dispersion relation; the level of significance; retaining wall; landslide; deformation prediction; дисперсионный аналіз; перемещения; дисперсионное отношение; уровень значимости; подпорная стенка; оползень; прогнозирование деформацій